Lidocaine 2% with adrenaline 1: 80,000 alkalinized with sodium bicarbonate 8.4 % in dental anesthesia - Victor Chumpitaz-Cerrate; Victoria Caldas Cueva; Cesar Ivanovish Franco Quino; Lesly Karem Chávez Rimache (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: The alkalinization of lidocaine has been successful in blocking the inferior dental nerve; however, there are contradictory results regarding its clinical efficacy. Objective: To determine the effect of 2% lidocaine with 1: 80,000 adrenaline alkalinized with 8.4% sodium bicarbonate on inferior dental nerve block. Material and methods: Experimental, prospective and longitudinal study that comprised 50 patients from the Dental School of the National University of San Marcos. The following solutions were administered for inferior dental nerve block: 2% lidocaine with epinephrine 1: 80,000 alkalinized with 8.4% sodium bicarbonate and 2% lidocaine with 1: 80,000 adrenaline not alkalinized. Pain intensity was evaluated by injection, hemodynamic parameters and anesthetic periods (time of onset of action and duration of the anesthetic effect). Results: There was a lower pain intensity due to injection in the alkalized lidocaine group (19.16 ± 2.7) compared to the non-alkalinized lidocaine group (22.88 ± 4.2); p=0.02. Likewise, the onset time of action was lower in the alkalized lidocaine group (105.72 ± 9.7) compared to the non-alkalinized lidocaine group (157.52 ± 12.1); p=0.002. However, no significant differences were found in the hemodynamic parameters (p>0.05) and the duration of the anesthetic effect (p=0.114). Conclusions: Lidocaine 2% with adrenaline 1: 80,000 alkalized with sodium bicarbonate at 8.4% on the block of the inferior dental nerve produces a decrease in pain intensity due to injection and the time of onset of action, compared to the non-alkalinized formulation. However, there are no differences in relation to the hemodynamic parameters or the duration of the anesthetic effect.